El concepto de educabilidad y el proceso educacional - García Carrasco, Joaquín (Teoría de la Educación. Revista Interuniversitaria, 2009)
The concept of educatability is reconsidered in this article. Instead of analysing it as a property of the structure itself or as a property of man, before all other considerations it may be understood as the opportunity that arises from the transaction between the individual and his/her environment. At the same time the primary mechanisms of the constitution of the opportunity of modifying man's behaviour are posed, taking into consideration the three major vectors by which the system of behaviours constituting a human being's personality has, on principle and from the very beginning, been affected: developmental processes, transactional processes and cultural processes.